Analisis Perkembangan Kurikulum di Indonesia (Sebuah Tinjauan Desain Dan Pendekatan) - Muhammad Nurhalim (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: Each curriculum should be organized and developed to fit the needs of the community so the curriculum is always required to be dynamic to follow the development of society and science, to change, to be corrected, even to have a renewal of continuous improvement. In the history of national curriculum development in Indonesia, the education in Indonesia has experienced several changes in the curriculum in 1947, 1950, 1968, 1975, 1984, 1994, 1999 supplement, 2004, and 2006. If the development of the curriculum is being observed, there are two main characteristics that could mark the changing those are from centralized to decentralized and from teacher to student centered. This paper attempts to examine the curriculum developments analysis in the review of design and approach. Keywords: curriculum development in Indonesia, the design and approach.